PEMBERDAYAAN MASYARAKAT MELALUI PENYULUHAN BUDIDAYA DOMBA DI KECAMATAN MONTONG: PEMBERDAYAAN MASYARAKAT MELALUI PENYULUHAN BUDIDAYA DOMBA DI KECAMATAN MONTONG - Afsah Indah Maulidah; Lia Nur Aini; Teguh Dwi Putra; Achmad Andi Nurifa'udin; Muhamad Baha'uddin (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2024)
The implementation of this service was carried out in Bringin Village, Montong District with an advanced scheme. If we look at the geographic location of Bringin Village, it is a village located in an inland area far from public transportation, so the majority of the people farm and raise livestock. Apart from that, this village has the potential for development, one of which is cultivating sheep to increase income. The methods used in implementing community service include outreach, counseling and evaluation. The result is that the community understands how to cultivate sheep properly starting from livestock cultivation management, livestock health and animal feed which can be managed by BUMDesa Bringin, Montong District. The Result, people of Bringin Village also gained understanding and insight into the benefits of sheep cultivation in order to increase community income.